2015
DOI: 10.1002/smll.201500940
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibers Comprising Yolk-Shell Sn@void@SnO/SnO2and Hollow SnO/SnO2and SnO2Nanospheres via the Kirkendall Diffusion Effect and Their Electrochemical Properties

Abstract: ZnO S. Sriram, M. Bhaskaran, and co-workers utilise oxygen-defi cient zinc oxide in stretchable devices to demonstrate sensing and photonic applications. On page 4532, interactions with the environment or with stimuli modify oxygen adsorption and, thereby, the carrier concentration. The resulting technology enables wearable UV and toxic gas sensors. Lithography High-precision leveling for polymer pen lithography is demonstrated by N.-J. Cho, S.-J. Cho, and co-workers with a 0.001° slope of feature edge-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 44 publications
1
65
0
Order By: Relevance
“…The three molecular-weight PVAs decomposed and were quickly transported towards the outer layer without carrying any of the inorganic materials. [76] By combining electrospinning with other methods, novel porous 1D nanostructures such as bubble-nanorod-structures [52,78,79] and bamboo-like structures [80] have been achieved. By this approach, other pea-like nanotubes including Co, LiCoO 2 , Na 0.7 Fe 0.7 Mn 0.3 O 2 and Li 3 V 2 (PO 4 ) 3 have been successfully synthesized as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three molecular-weight PVAs decomposed and were quickly transported towards the outer layer without carrying any of the inorganic materials. [76] By combining electrospinning with other methods, novel porous 1D nanostructures such as bubble-nanorod-structures [52,78,79] and bamboo-like structures [80] have been achieved. By this approach, other pea-like nanotubes including Co, LiCoO 2 , Na 0.7 Fe 0.7 Mn 0.3 O 2 and Li 3 V 2 (PO 4 ) 3 have been successfully synthesized as well.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the porosity of porous nanowires is also adjustable via the control of annealing temperature. [78,79] A second example of combining methods, a bamboo-like graphitic carbon nanofiber with well-balanced macro-, meso-, and microporosity, was prepared by Cui and co-workers. [76] By combining electrospinning with other methods, novel porous 1D nanostructures such as bubble-nanorod-structures [52,78,79] and bamboo-like structures [80] have been achieved.…”
Section: Methodsmentioning
confidence: 99%
“…To date, zero- (0D), one- (1D), two- (2D), and three-dimensional (3D) hollow nanostructures with various compositions have been developed based on the requirements of the various applications891011121314151617. Generally, spherical (0D) and non-spherical (1D, 2D, and 3D) hollow nanostructures are prepared by the application of removable organic and inorganic templates in liquid solution processes1314151617.…”
mentioning
confidence: 99%
“…Resulted structures such as yolk-shell, SnO/SnO 2 and SnO 2 nanospheres-based nanofibers show capacity of 663, 630 and 567 mAh g -1 after 250 cycles with capacity retention of 77%, 84% and 78%, respectively. [177] Thus, these results have clearly shown that composition, structure and morphology have different effect on the capacity and capacity retention of anode materials. Yang et al have introduced another approach to control over structural changes and to improve the electrochemical performance by combining hard inactive material (Fe 3 C) with electrochemically active (Fe 2 O 3 ) materials.…”
Section: Metal Oxides As Anode Materialsmentioning
confidence: 94%
“…Further, Cho et al utilized Kirkendall diffusion process to prepare complex morphologies and structures to stabilize the performance of Sn and SnO 2 . [177] They have prepared nanofibers of Sn@void@SnO/SnO 2 yolkshell structures and hollow SnO/SnO 2 and SnO 2 nanospheres by simple oxidation of Sn-C composite nanofibers at different temperatures 400 °C, 500 °C and 600 °C, respectively under air atmosphere. Resulted structures such as yolk-shell, SnO/SnO 2 and SnO 2 nanospheres-based nanofibers show capacity of 663, 630 and 567 mAh g -1 after 250 cycles with capacity retention of 77%, 84% and 78%, respectively.…”
Section: Metal Oxides As Anode Materialsmentioning
confidence: 99%